THE NUTRITION INTAKE CONTROL TOOLS IN HYDROPONIC USING MICROCONTROLLER - Sauthul Fikri; Arief Budi Laksono; Ulul Ilmi (Merdeka Malang University, 2021)
The development of the world of technology combined with agricultural science can benefit farmers and, of course, the community. one of them is farming through the Hydroponic system, the purpose of this study is to find out how to make nutrition control devices on the Pakcoy hydroponics using a microcontroller on hydroponics. The method used includes electrical design, systematic, in order to obtain accurate data and information. This study using the stages of designing hardware and software and integrating the system and the system testing stage. This test uses a pH meter, where the sensor detects a pH with a value of 6-7 pH, and when the pH sensor detects a value below six, it will automatically add nutrients. As well as water temperature and room temperature will regulate the temperature in the water by turning on the waterwheel in the reservoir automatically. Furthermore, all results are sent to the ThinkSpeak application via an IoT server. The display produced on ThinkSpeak is the water temperature, room temperature, water temperature, and water pH.